Frequency of neoplasms in mammary gland of canines diagnosed histopathologically in the Faculty of Veterinary Medicine of the Universidad Nacional Mayor de San Marcos, period 2007- 2016 - Lipa C., Julisa (2019)
The aim of this retrospective study was to determine the frequency of neoplasms in the mammary gland of canines whose histopathological diagnosis was made in the Animal Histology, Embryology and Pathology Laboratory of the Faculty of Veterinary Medicine of the Universidad Nacional Mayor de San Marcos (Lima, Peru). Reports were collected from 2007 to 2016, considering the variables sex, breed, age, location and histopathological diagnoses. The histological slides were classified according to Goldschmidt et al. (2011). The total of neoplastic processes in canines was 1599, where 359 corresponded to mammary gland neoplasms (22.4 ± 2.04% IC0.95). The females were the most affected (98%), while the proportion of mestizo dogs affected was 32% and 68% belonged to pure breeds, mainly Cocker (13%), Boxer (5.9%), Labrador (5.4%) and Yorkshire (4.5%). Canines of 10 years old were the most affected (17.7%), and the 9 and 12 years was the most affected stratum age (49.3%). In addition, 60.6% of mammary neoplasms occurred in the fourth and fifth mammary glands and 94.7% of mammary tumors presented malignant histological features, with cystic papillary carcinoma being the most frequent histopathological type (42.8%), followed by tubular carcinoma (13.9%).